Political Economy Of Rubber in Peru: A Literature Approximation - Pennano, Guido (1978)
The study of the rubber industry and its economic and social consequences in Peru, allow us to rethink a series of arguments that we believe are of some importance to understand more clearly the true sense of the process of national and regional underdevelopment in Peru. The rubber is not more than one additional case in the long list of "booms-product" that the country has suffered throughout its history.